Paradox, Dialectics or Trade‐Offs? A Double Loop Model of Paradox - Berti, Marco; Cunha, Miguel Pina e (Journal of Management Studies, 2023)
Paradox literature is emerging as one of the most vital streams in management studies, but it is affected by some growing pains. First, the concept of paradox is still too fuzzy, which impacts empirical research and hinders communication with other literatures. Second, the assumption that paradoxes are always best met with acceptance and search for balance is problematic because it limits the heuristic potential of a paradox lens, because it constrains the range of sustainable responses to contradictions, and because it may induce to appeasement in face of injustice. In this paper we propose to strengthen paradox theory by incorporating the contributions of two alternative perspectives on organizational tensions: trade‐offs and dialectics. We thus present a model which expands organizational paradox theory by: (1) clarifying the concept of organizational paradox; and (2) offering a model that better describes the varied phenomenology, causes and consequences of organizational tensions and paradoxes.